If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -2 + 3 = 6 + 11 Reorder the terms: -2 + 3 + X = 6 + 11 Combine like terms: -2 + 3 = 1 1 + X = 6 + 11 Combine like terms: 6 + 11 = 17 1 + X = 17 Solving 1 + X = 17 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + X = 17 + -1 Combine like terms: 1 + -1 = 0 0 + X = 17 + -1 X = 17 + -1 Combine like terms: 17 + -1 = 16 X = 16 Simplifying X = 16
| f(x)=2(x-1)(x-6) | | 3x=7x+84 | | 4x+2(x+6)=4(x-2)-26 | | 5+3x=155x | | 8v-74=7v-61 | | x^2-36=y | | 16=3y+5y | | -16x^2+70x+5=-4 | | 32=5y+3y | | x+9(x-2)=2-3(1-2x) | | x+1/2=(x-2)2-1/2 | | 0.5x+y=4.5 | | 2+3t=3+4s | | 6(2-x)-(3-x)=7(2x+3) | | 3x^2+57=0 | | a+2(a+3)=9 | | 17=4p-3 | | H=-16t^2+32+5 | | 1000*.01*5= | | 18=4y+2y | | 4x=x^2+42 | | 2x^2+57=0 | | 9/11-5/11= | | 136*5= | | 1700*.08= | | -7/16x1/7 | | 2x+5,1=3(x-4,2) | | 0=0-5x | | 4x^2-1/x=0 | | 5x=(-1/5) | | 6x+9+2x+8=25 | | 2(x-3)+48x+5=6 |